1994
DOI: 10.1002/mde.4090150305
|View full text |Cite
|
Sign up to set email alerts
|

Ownership effects on operating strategies: Evidence of expense‐preference behavior in the hospital industry

Abstract: Expense preference offers an alternative to profit‐maximization theory in explaining firms' operating strategies (Williamson, 1963; Rees, 1974). Expense‐preference theory suggests that when disctretionary behavior is allowed, corporate managers may choose to maximize individual utility instead of corporate profit. Expense‐preference behavior tends to be evidenced by higher expenditures on items for which managers have a positive personal preference than would be justified by profit maximization. Conditions und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…There is strong support from previous research that being highly regulated can give managers more opportunity to exhibit expense preference behavior (Gropper & Hudson, 2003;Gropper & Oswald, 1996;Mixon & Upadhyaya, 1996;Williamson, 1963). The fact that over three-fourths of the casinos are publicly owned shows that these firms have a high possibility of a greater separation of ownership, which is also supported by previous research to give managers a chance to exhibit expense preference behavior (Akella & Greenbaum, 1988;Oswald et al, 1994;Verbrugge & Goldstein, 1981;Verbrugge & Jahera, 1981).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…There is strong support from previous research that being highly regulated can give managers more opportunity to exhibit expense preference behavior (Gropper & Hudson, 2003;Gropper & Oswald, 1996;Mixon & Upadhyaya, 1996;Williamson, 1963). The fact that over three-fourths of the casinos are publicly owned shows that these firms have a high possibility of a greater separation of ownership, which is also supported by previous research to give managers a chance to exhibit expense preference behavior (Akella & Greenbaum, 1988;Oswald et al, 1994;Verbrugge & Goldstein, 1981;Verbrugge & Jahera, 1981).…”
Section: Resultssupporting
confidence: 63%
“…Researchers believe that not-for-profit managers will spend more because not-for-profit firms cannot make money for their owners, although the results are mixed. Oswald, Gardiner, and Jahera (1994) and Carter et al (1997) show that managers under a not-forprofit structure spend more than those under a proprietary structure, while Lewin et al (1981) find different results depending on what expenses they evaluate. Becker and Sloan (1985) believe it is important to control for other firm differences besides just ownership structure.…”
Section: Ownership Structurementioning
confidence: 99%
“…The agency theory also sheds light on the traditional 'expensepreference' theory (e.g. Oswald et al 1994). 9.…”
Section: Discussionmentioning
confidence: 99%
“…Leggett and Strand (2002) found that the wave of mergers and rapid growth in size of United States credit unions that followed the 1982 elimination of multiple bond restriction, is resulting in measurable increase in 'agency costs' -a parallel concept proposed by Jensen and Meckling (1976). The effect was also found in the United States Savings and Loans sector (Mester 1989, 1991, Verbrugge and Goldstein 1981, Verbrugge and Jahera 1981, in other industries (Oswald and Gardiner 1994, Awh and Primeaux 1985, Rhoades 1980 and in mutual property liability insurance firms (Cummins, Weiss and Zi 1999).…”
Section: A Review Of the Tce Based Theory Of Cooperative Networkmentioning
confidence: 99%